Practice of dilatation after surgical correction in anorectal malformations - Jenetzky, Ekkehart; Reckin, S.; Schmiedeke, Eberhard; Schmidt, Dominik; Schwarzer, Nicole; Grasshoff-Derr, Sabine; Zwink, Nadine; Bartels, Enrika; Rißmann, Anke; Leonhardt, Johannes; Weih, Sandra; Obermayr, Florian; et al. (Pediatric surgery international, 2012)
BackgroundIn order to prevent stricture of the neoanus after surgical correction, regular dilatation is recommended. There is a lack of knowledge about the performance of anal dilatation and the occurrence of pain. The aim of our investigation was to describe the practice of dilatation and to identify possible risk factors for painful procedures.MethodsCongenital Uro-Rectal Malformations Network is a German interdisciplinary multicenter research network. With standard questionnaires, physicians interviewed 243 patients and/or their parents at home, additional 103 patients born since 2009 were assessed through their treating physicians.ResultsIn total, 88 % of the patients received dilatations. Treatment lasted for 7 months in median (range 1-156 months), until the age of 13 months (range 1-171 months). In 69 % painful dilatation was reported; without a significant differences in age or gender. In 32 % bleeding was reported. In 30 % at least one dilatation was performed under general anesthesia. In 11 % some kind of analgesia was used. Type of fistula, dilatations lasting longer than 10 months and Hegar size above 15 were relevant factors for experience of pain. There were about 16 % postoperative strictures of the neoanus, without reported differences in dilatation procedures; but there was a relation to type of malformation.ConclusionConsidering the high number of painful treatments, predictors for painful dilatations should be further clarified through standardized documentation and prospective evaluation in order to improve follow-up.